Nasal obstruction and positional obstructive sleep apnea - Panprapakorn, Kornkla; Hirunwiwatkul, Prakobkiat; Chaitusaney, Busarakum; Charakorn, Natamon (Chulalongkorn Medical Journal, 2022)
Background: Nasal obstruction is one of common risk factors of obstruction in obstructive sleep apnea (OSA) which can be caused by structural abnormalities. Positional obstructive sleep apnea (POSA) is defined that severity of OSA will be worsen in supine position. However, the correlation between nasal obstruction and POSA are unclear. Objectives: The aim of this study was to investigate the prevalence of nasal obstruction in OSA patients and find the correlation between nasal obstruction and respiratory disturbance index (RDI) in these subjects. We also aimed to determine find the correlations in OSA patients POSA and those without POSA. Methods: This study was a descriptive study that collected data form medical records and polysomnography. A total of 340 OSA patients were recruited in the study. All of them underwent overnight polysomnography and nasal examination. We defined the severity of nasal obstruction (nasal septum deviation and inferior turbinate hypertrophy) for 4 grades: normal, mild, moderate and severe obstruction. Correlations between nasal obstruction and RDI were calculated. Results: The prevalence of nasal obstruction in OSA patient was 77.6 %. Nasal obstruction was not correlated with severity of OSA in all parameters. RDI of 128 POSA patients was significantly correlation with nasal septum score (r = 0.196, P = 0.027) and total nasal obstruction score (r = 0.203, P = 0.022). Conclusion: The prevalence of nasal obstruction in Thai OSA patients was high. Total nasal obstruction score and nasal septum deviation was found to be significantly correlated with the severity of POSA. Nasal examination is essential to identify nasal pathology and beneficial in OSA patients, especially POSA.